Drift Instability In Flows of Dusty Plasma with Continuous Size Spectrum of Grains - Yaroshenko, V. V. (Видавничий дім «Академперіодика», 2012)
Drift Instability In Flows of Dusty Plasma with Continuous Size Spectrum of Grains